Impaired autophagy increases susceptibility to endotoxin-induced chronic pancreatitis - Xia, Leizhou; Xu, Zhen; Zhou, Xiaodong; Bergmann, Frank; Grabe, Niels; Büchler, Markus W.; Neoptolemos, John P.; Hackert, Thilo; Kroemer, Guido; Fortunato, Franco (Cell death & disease, 2020)
Chronic pancreatitis (CP) is associated with elevated plasma levels of bacterial lipopolysaccharide (LPS) and we have demonstrated reduced acinar cell autophagy in human CP tissue. Therefore, we investigated the role of autophagy in experimental endotoxin-induced pancreatic injury and aimed to identify LPS in human CP tissue. Pancreatic Atg7-deficient mice were injected with a single sub-lethal dose of LPS. Expression of autophagy, apoptosis, necroptosis, and inflammatory markers was determined 3 and 24 h later utilizing immunoblotting and immunofluorescence. The presence of LPS in pancreatic tissue from mice and from patients and healthy controls was determined using immunohistochemistry, immunoblots, and chromogenic assay. Mice lacking pancreatic autophagy exhibited local signs of inflammation and were particularly sensitive to the toxic effect of LPS injection as compared to control mice. In response to LPS, Atg7Δpan mice exhibited enhanced vacuolization of pancreatic acinar cells, increase in TLR4 expression coupled to enhanced expression of NF-κΒ, JNK, and pro-inflammatory cytokines by acinar cells and enhanced infiltration by myeloid cells (but not Atg7F/F controls). Cell death was enhanced in Atg7Δpan pancreata, but only necroptosis and trypsin activation was further amplified following LPS injection along with elevated pancreatic LPS. The presence of LPS was identified in the pancreata from all 14 CP patients examined but was absent in the pancreata from all 10 normal controls. Altogether, these results support a potential role for metabolic endotoxemia in the pathogenesis of CP. Moreover, the evidence also supports the notion that autophagy plays a major cytoprotective and anti-inflammatory role in the pancreas, and blunting metabolic endotoxemia-induced CP.
Gesehen am 30.11.2020